Individualized Biventricular Epicardial Augmentation Technology in a Drug-Induced Porcine Failing Heart Model. Issue 4 (July 2018) - Jagschies, Lasse; Hirschvogel, Marc; Matallo, Jose; Maier, Andreas; Mild, Karin; Brunner, Horst; Hinkel, Rabea; Gee, Michael W.; Radermacher, Peter; Wildhirt, Stephen M.; Hafner, Sebastian
Abstract : For treatment of advanced heart failure, current strategies include cardiac transplantation or blood-contacting pump technology associated with complications, including stroke and bleeding. This study investigated an individualized biventricular epicardial augmentation technology in a drug-induced porcine failing heart model. A total of 11 pigs were used, for the assessment of hemodynamics and cardiac function under various conditions of support pressures and support durations (n = 4), to assess device positioning and function by in vivo computer tomographic imaging (n = 3) and to investigate a minimally invasive implantation on the beating heart (n = 4). Support pressures of 20–80 mm Hg gradually augmented cardiac function parameters in this animal model as indicated by increased left ventricular stroke volume, end-systolic pressures, and decreased end-diastolic pressures. Strong evidence was found regarding the necessity of mechanical synchronization of support end with the isovolumetric relaxation phase of the heart. In addition, the customized, self-expandable implant enabled a marker-guided minimally invasive implantation through a 4 cm skin incision using fluoroscopy. Correct positioning was confirmed in computer tomographic images. Continued long-term survival investigations will deliver preclinical evidence for further development of this concept. Abstract : Supplemental Digital Content is available in the text.